2018
DOI: 10.3390/molecules23112970
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Synthesis, Characterization and Biological Evaluation of Some Novel Pyrazolines Containing Thiazole Moiety as Potential Anticancer and Antimicrobial Agents

Abstract: The one-pot synthesis of a series of pyrazoline derivatives containing the bioactive thiazole ring has been performed through a 1,3-dipolar cycloaddition reaction of N-thiocarbamoylpyrazoline and different hydrazonoyl halides or α-haloketones in the presence of DABCO (1,4-diazabicyclo[2.2.2] octane) as an eco-friendly catalyst using the solvent-drop grinding method. The structure of the synthesized compounds was elucidated using elemental and spectroscopic analyses (IR, NMR, and Mass). The activity of these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Edrees et al documented recently the synthesis and anticancer screening against HepG 2 human hepatocellular carcinoma cell line of a library consisting of 19 pyrazoline derivatives bearing a thiophenyl group at C-3 [ 114 ]. The structures were divided in three groups depending on the exact formula of the thiazole unit; thiazoles incorporating an acyclic nitrogen-nitrogen double bond group, thiazolones, and arylsubstituted thiazoles.…”
Section: 2-pyrazolinesmentioning
confidence: 99%
“…Edrees et al documented recently the synthesis and anticancer screening against HepG 2 human hepatocellular carcinoma cell line of a library consisting of 19 pyrazoline derivatives bearing a thiophenyl group at C-3 [ 114 ]. The structures were divided in three groups depending on the exact formula of the thiazole unit; thiazoles incorporating an acyclic nitrogen-nitrogen double bond group, thiazolones, and arylsubstituted thiazoles.…”
Section: 2-pyrazolinesmentioning
confidence: 99%
“…[ 29 ] Also, pyrazoline derivatives exhibit pharmacological activities such as antitumor, [ 30 ] antibacterial, [ 31 ] anti‐inflammatory, [ 32 ] antifungal, [ 33 ] and antidepressant activities [ 15 ] (Figure 2). Recent studies have revealed that thiazolyl‐pyrazoline derivatives show potent antifungal, [ 34 ] antibacterial, [ 29 ] and antioxidant [ 35 ] activities, in addition to inhibitory effects on the epidermal growth factor receptor tyrosine kinase as a target for anticancer therapy, [ 36–39 ] among others. [ 18 ] For example, Altintop et al [ 34 ] reported that novel thiazolyl‐pyrazolines bearing thiophenes showed antifungal activity against different Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…Among the variety of heterocyclic products, pyrazolines have been the most significant scaffolds among the azole family because of their pharmacological applications . These compounds act as highly beneficial bactericidal and fungicidal agents . Pyrazoles are also found to act as COX‐2/B‐Raf, aurora kinase, EGFR‐TK, and tubulin assembling inhibitors along with their anticancer properties .…”
Section: Introductionmentioning
confidence: 99%